College students responding to the Chinese version of Cardiff fertility knowledge scale show deficiencies in their awareness: a cross-sectional survey in Hunan, China - Yanhui Zhou; Yang Luo; Ting Wang; Yanhui Cui; Mingzhu Chen; Jingxia Fu (BMC, 2020)
Abstract Background Fertility knowledge is vital to the fertility health of young people and greatly impacts their fertility choices. Delayed childbearing has been increasing in high-income countries, accompanied by the risk of involuntary childlessness or having fewer children than desired. The aim of this study was to investigate knowledge about fertility issues, the related influencing factors, the method of acquiring fertility knowledge, and the relationship between fertility knowledge and fertility intentions among college students. Methods An online cross-sectional survey of Chinese college students was conducted in Hunan Province from March to April 2018. A total of 867 college students from three comprehensive universities responded to a poster invitation utilizing the Chinese version of the Cardiff Fertility Knowledge Scale (CFKS-C). Data were explored and analysed by SPSS (version 22.0) software. Descriptive statistics, chi-squared tests, T-tests, and Pearson's correlations were used for the measurements. Results The average percent-correct score on the CFKS-C was 49.9% (SD = 20.8), with greater knowledge significantly related to living in a city district, being not single status, majoring in medicine, being in year 4 or above of study, and intention to have children (all p<0.05). A total of 81.9% of the participants reported that they would like to have children, the average score of the importance of childbearing was 6.3 (SD = 2.7), and the female score was lower than the male score (p = 0.001). A small positive relationship was observed between the CFKS-C and the importance of childbearing (r = 0.074, p = 0.035). Respondents indicated that they gained most of their knowledge from the media and internet (41.4%) and from schools (38.2%). Conclusion Yong people in college have a modest level of fertility knowledge, a relatively low intention to have a child, and deficiencies in fertility health education. There is a need to improve the accessibility of fertility health services by developing a scientific and reliable fertility health promotion strategy.